Acetylpyrene-labelled 7-methylguanine nucleotides: unusual fluorescence properties and application to decapping scavenger activity monitoring. Issue 16 (15th March 2016) - Kasprzyk, Renata; Kowalska, Joanna; Wieczorek, Zbigniew; Szabelski, Mariusz; Stolarski, Ryszard; Jemielity, Jacek
Abstract : We describe acetylpyrene-labeled mRNA cap analogues with untypical fluorescent properties as probes for inhibitor screening of DcpS. Abstract : 7-Methylguanosine (m 7 G) nucleotides labelled with acetylpyrene (AcPy) were synthesized as fluorescent mRNA 5′ end (cap) analogues. The unique fluorescent properties of m 7 G–AcPy conjugates, different from G–AcPy, can be applied to studying various mRNA cap-related processes including the evaluation of putative inhibitors of DcpS enzyme—a therapeutic target in neuromuscular diseases.